Implantación del sistema contable en farmacia “Familiar” de la ciudad de Cariamanga, cantón Calvas, provincia de Loja periodo enero-febrero 2015 - Preciado Cueva, Maily Elizabeth (2016)
This thesis entitled: IMPLEMENTATION OF ACCOUNTING SYSTEM IN "FAMILY" CITY Cariamanga PHARMACY Region bald Loja province PERIOD JANUARY-FEBRUARY 2015 was developed in order to help its owner to optimize the economic performance of its business, and to comply with the Rules of Academic System of the National University of Loja and one of the pre-choose the degree of Engineer in Accounting and Auditing, CPA at the National University of Loja requirements. By developing this research were complied with the objectives, first we proceeded to collect information which could be performed to determine the inventory of goods, values, rights and obligations of pharmacy; then the plan and manual analysis, according to the needs of "Family" Pharmacy was designed; then the various documents and auxiliary and main accounting records, such as Kardex cards, sales annexes, depreciation tables, journal, ledger, trial balance, worksheet, allowing the implementation of the accounting process was developed. At the end of this research work it is determined that the lack of an accounting system prevents control of economic movements and financial situation of "Family" pharmacy whose RUC is 1102799549001, which makes it important to implement the proposed accounting system, it will facilitate generating real and timely financial statements, which let you know the results and facilitate management decision making.